Organic Farming in Tirupur City - Karpagavalli, V. (AMC Indian Journal of Entrepreneurship, 2018)
Organic foods are foods that are produced using methods that do not involve modern synthetic inputs such as synthetic pesticides and chemical fertilizers. Organic foods are also not processed using irradiation, industrial solvents, or chemical food additives. The weight of the available scientific evidence has not shown a consistent significant difference between organic and more conventionally grown food in terms of safety, nutritional value or taste. For the vast majority of its history, agriculture can be described as having been organic; only during the 20th century was large supply of new â€œchemicalsâ€ introduced.Â  The organic farming movement started in the 1940s in response to the industrialization of agriculture known as the green revolution.